Research on Rule Hiding Algorithm of Transaction Adding and Removing - Xiaoming Zhang (Proceedings : Fourth International Conference on Fuzzy Systems and Knowledge Discovery : FSKD 2007, 24-27 August 2007, Haikou, Hainan, China, 2007)
A new approach by transaction adding and removing (TAR) is presented for association rule hiding. Only a few transactions need updating to the mined dataset. Firstly, two definitions of weak associated transaction (WAT) and strong associated transaction (SAT) are defined. Then, the TAR approach and algorithm are stated in detail with two main processes of WAT adding and SAT removing. Two selections of modifying item are studied for single rule and multiple rules hiding. And two kinds of WAT modifying approaches are described and compared to avoid the transaction duplication in the database. Based on the detail experimental results, the data type modifying approach can be always better than the Unknown approach. The side effects of the TAR algorithm are usually lower than 15% when the hiding rate reaches to 100%. The algorithm can be suitable for single rule and multiple rules hiding.